Pengaruh Kompleksitas Operasi, Komite Audit dan Kepemilikan Publik Terhadap Audit Delay: Studi Empiris pada Emiten Sektor Properties & Real Estate Periode 2020-2023 - Ninda Sherly Anggraini; Istianingsih Sastrodiharjo; Aloysius Harry Mukti; Bambang Prayogo (Universitas 45 Surabaya, 2025)
This study aims to analyze the effect of operating complexity, audit committee, and public ownership on audit delay in property and real estate sector companies in Indonesia during the period 2020-2023. This study used a sample of 71 companies selected by purposive sampling method. This research uses descriptive statistical techniques with a quantitative approach. The analysis and testing tools used in this study are Descriptive Statistical Test, Classical Assumption Test, which consists of Normality Test, Multicollinearity Test, Heteroscedasticity Test, and also Autocorrelation Test. The results show that operating complexity and public ownership have a positive effect on audit delay, while the audit committee has no significant effect